Role of angiotensin converting enzyme, paraoxonase 1 55,192 gene polymorphisms in syndrome X and coronary heart disease - SESAL, NÜZHET CENK (My University, 2009)
Aim of this study was to investigate the possible relationship between ACE and/or P0N1 M55L, Q192R genetic polymorphisms and subjects with Coronary Heart Disease (CHD) and/or syndrome X (SX) when compared to the control group. ACE I/D, PON1 M55L and Q192R genetic polymorphisms, Body Mass Index (BMI) and biochemical parameters were investigated in subjects with CHD (n = 19), SX (n = 34) and healthy subjects (n = 26). All of the subjects were nonsmokers. According to the unrelated group t-test results; BMI, HDL-C and TG values were found to be slightly different in SX and control subjects but there was no significant difference in LDL-C and TC values. According to the Mann Whitney U-test results, BMI, TC, HDL-C and LDL-C values were found to be significantly different among CHD and control group subjects, but there was no difference in TG values. The results of this study indicates that ACE, PON1 192 and PON1 55 gene polymorphisms are not related to genetic susceptibility to SX and/or CHD in non-smokers. Obviously, the interpretation of these finding is difficult due to the small sample size and larger group studies are needed for more definitive conclusions © 2009 Asian Network for Scientific Information.
Keywords: Angiotensin converting enzyme; Coronary heart disease; Genetic polymorphism; Paraoxonase 1; Syndrome X